Análise de QTLs e herança de caracteres associados à qualidade de melão - Dantas, Ana Carolina de Assis (2015)
The quality of the melon is one of the main objectives of breeding programs. An important aspect for the breeder is to know its inheritance as it assists in choosing the breeding strategy with time and resource savings. In addition, the use of biotechnological tools to assist in the knowledge of architecture of the characters and facilitate the selection process may be useful. The objectives of this study were: to identify SSR markers linked to QTLs of six characters related to the quality of melon and to study the genetic control of traits related to fruit quality of melon through classic study of generations involving mixed models. Based on this, we evaluated 100 F2: 3 families of crossing between the parents 'Hales Best Jumbo' (HBJ) and 'MR-1', momordica type, in the years 2013 and 2014. For the phenotypic evaluation of the families, two experiments were carried out in randomized block design with three replications. Each plot consisted of a line with five plants, spaced 2.0 m between rows and 0.3 m between plants. The traits evaluated were: fruit weight, shape index, flesh thickness, flesh firmness, soluble solids and percentage of fruit cracking. From the results, the identification of stable molecular markers linked to quality traits of melon fruit through multiple regression procedure was possible. Using multiple regression process were identified markers associated to the average fruit weight characters, shape index, flesh thickness, firmness, soluble solids and percentage of fruit cracking. The CMMS22-2, CMCTN4 and CMMS4-3 markers were the most stable in both evaluations. The CMGAN3 markers, CMAGN33, CMSTN4, CMMS4-3, CMMS22-2 were those who stood out as the most promising for assisted selection to improve the melon quality. For the inheritance study, the generations F1, F2 and backcross of crossings OL x A-16 and OL-PV were evaluated in two separate experiments carried out in randomized block design with three replications, in 2012. The traits evaluated were: average fruit weight, shape index, flesh thickness, flesh firmness and soluble solids. The analyses were performed using mixed models to estimate the parameters of the additive-dominant model and the variance components. The heritability in the narrow and broad sense and number of loci that control the character were estimated. Maximum likelihood hierarchical genetic models were used in tests of hypothesis in order to assess the presence of polygenes and major effect gene in the genetic control character. From the results, it is concluded that the inheritance of the studied characters is complex, with the presence of major gene and polygenes with additive and dominance effects